Ultrasonograph and Clinical Quantitative Characterization of Tendinopathy by Modified Splitting in a Goat Model - A. Kavaguchi De Grandis; C. Boulocher; E. Viguier; T. Roger; S. Sawaya (The Scientific World Journal)
A tendinopathy is a clinical condition characterized by activity-related pain, focal tendons tenderness, and intratendinous imaging changes. This study characterizes a surgically induced tendinopathy in a goat model with a noninvasive in vivo longitudinal followup based on physical examination and US. Cross-sectional area (CSA) is the most objective feature for the evaluation of tendinopathy in correlation with clinical findings. The deep digital flexor tendon (DDFT) of the left hind limb of six goats was isolated and scarified by a modified splitting. Pain and lameness at walk and trot were evaluated. External width and thickness of tendon region were measured by calipers. CSA and the ratio lesion/tendon CSA were obtained at days 0, 7, 21, 42, and 84 by US. The highest value of global functional score was obtained at day 7, then decreased until day 40 and was not significantly different from day 0 at the end of the study. The external width recovered a normal value at the end of the study, but the external thickness was still significantly increased (P<0.05). Peritendinous oedema was observed at day 7, but intratendinous lesions were visible only at day 21 as a focal hypo to anechoic area. At day 84, two tendons still presented visible lesions. US examination was reproducible, specific, and provided complementary information to the global functional score. A standardized focal tendinopathy was induced in goats. This experimental model of focal tendinopathy could be used to study the effect of different treatments.